Research on Intelligent Stress Analysis and Safety Assessment Model of BIM-FEM Formwork Support System - Li, Jidong; Chen, Shi; Wang, Zeyu; Dong, Hao; Wang, Gang; Ma, Hanjun (Informatica, 2025)
With the rapid development of the construction industry, the safety and stability requirements of formwork support systems during construction have become increasingly strict. The purpose of this study is to integrate BIM (Building Information Modeling) and FEM (Finite Element Method) to develop an intelligent force analysis and safety assessment model to improve the design and construction safety of formwork support systems. Through BIM technology, the accurate modelling of the bracket system is realized and combined with FEM for force analysis, the model shows high-precision performance under various load conditions, and the force analysis error is reduced by 15% compared with traditional methods. After the machine learning algorithm is introduced, the model can automatically optimize the parameters of the bracket, and the experimental results show that the displacement of the optimized bracket under the ultimate load is reduced by 20%, significantly improving the bracket’s stability. In the comprehensive safety assessment test, the model successfully identified three potential safety hazards and provided effective rectification suggestions, effectively preventing safety accidents in practical application. This study not only promotes the application of BIM and FEM in formwork support systems but also provides a new technical path for the intelligent development of the construction industry.